Literasi Keuangan, Sikap Keuangan dan Perilaku Keuangan dan Kinerja UMKM - Irin Fitria; Fransiska Soejono; M J Tyra (Journal of Business & Banking, 2021)
This study aims to examine the effect of financial literacy variables, financial attitudes, and financial behavior on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Palembang city. The respondents who were involved were 115 MSMEs. The data were collected using an online questionnaire, namely google form. This research uses the validity test to test the research instrument, the reliability of the research questionnaire, and test the classical assumptions to fulfill the research regression model which is the Best Linear Unbiased Estimator. They were analyzed using Multiple regression models and research hypothesis testing was also done. The Financial literacy of MSMEs owner is moderate, while their financial attitudes and behavior are relatively good. The findings show that financial attitudes have a positive effect on the performance of MSMEs. Another finding shows that financial literacy and financial behavior have no effect on the performance of MSMEs. MSMEs owners need to develop good financial attitudes in managing their businesses so that the achievement of business performance is more optimal.